2013
DOI: 10.1002/srin.201300039
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior of Low Carbon Steel at Elevated Temperature in Oxygen and Water Vapor

Abstract: Oxidation behavior of low carbon steel was investigated in oxygen and water vapor using continuous thermogravimetric analysis (TGA). The effect of temperature, oxygen pressure, and water vapor content on the oxidation of the steel was studied. The morphology, composition, and microstructure of oxides formed in moist atmosphere were examined and analyzed by X‐ray diffraction (XRD), scanning electron microscope (SEM), and energy dispersive X‐ray analysis (EDX). The oxidation mechanism was discussed based on oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The previous investigations have revealed that wet CO 2 usually produce oxide scales with more defects such as microcracks, voids and pores, which allow increased penetration paths of the oxidizing gases to the interface between the oxide scale and substrate. These oxidizing gases will react directly with pure iron and accelerate the entire oxidation rate . The oxide scale also tends to delaminate more easily than that formed in air due to accumulated growth stress inside.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous investigations have revealed that wet CO 2 usually produce oxide scales with more defects such as microcracks, voids and pores, which allow increased penetration paths of the oxidizing gases to the interface between the oxide scale and substrate. These oxidizing gases will react directly with pure iron and accelerate the entire oxidation rate . The oxide scale also tends to delaminate more easily than that formed in air due to accumulated growth stress inside.…”
Section: Resultsmentioning
confidence: 99%
“…These oxidizing gases will react directly with pure iron and accelerate the entire oxidation rate. 15,16 The oxide scale also tends to delaminate more easily than that formed in air due to accumulated growth stress inside.…”
Section: Methodsmentioning
confidence: 99%
“…The controlled humid atmosphere is produced by passing dry air pass through a sealed water tank held at a given temperature. The maximum water temperature for WETSYS is 60 °C (corresponding to 20% water vapor in water‐saturated gas), which is used in this investigation . As a comparison, the oxidation behaviors of the IC are also investigated in dry air.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum water temperature for WETSYS is 60 8C (corresponding to 20% water vapor in water-saturated gas), which is used in this investigation. [18] As a comparison, the oxidation behaviors of the IC are also investigated in dry air. The schematic diagram of the apparatus is illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Yun et al showed that for oxidation of a low carbon steel at 500 °C, wustite was not detected, whereas wustite was dominant layer for oxidation at 700 °C. Also, Yun et al acquired higher oxygen rate for oxygen containing water vapor compared with those in dry gases. Carbon is the most important alloying element influencing the oxidation kinetics .…”
Section: Introductionmentioning
confidence: 99%